Class III obesity is an independent risk factor for unsuccessful induction of laborAJOG Global Reports at a Glance - Rosa Drummond, MD; Mayuri Patel, BS; Madalyn Myers, BS; Alexandra Ritter, MA; Julie A. Hurvitz, MD; Katherine R. Goetzinger, MD, MSCI; Sarah D. Crimmins, DO (Elsevier, 2022)
BACKGROUND: Although obesity is a known risk factor for cesarean delivery, there is a paucity of data on the course of induction of labor in these patients. OBJECTIVE: With emerging data on the safety of 39-week inductions, we aimed to: (1) determine if Class III obesity, including morbid obesity, is an independent risk factor for nonachievement of complete dilation and vaginal delivery after induction of labor, (2) evaluate the characteristics of the induction of labor course and immediate complications, and (3) evaluate the number of induction agents necessary to be associated with vaginal deliveries. We hypothesized that as body mass index increased, it would take longer to achieve complete cervical dilation, more induction agents would be required, and there would be a higher rate of cesarean delivery. STUDY DESIGN: This was a retrospective cohort study of singleton gestations undergoing induction of labor from 2013 to 2020 at a single center. Study groups were defined as nonobese (body mass index <30 kg/m2), non-Class III obesity (body mass index of 30-39.9 kg/m2), and Class III obesity (body mass index ≥40 kg/m2). The primary outcome was achievement of complete cervical dilation. Secondary outcomes included time from start of induction to complete dilation, cesarean delivery rates, doses of misoprostol used, combination of induction agents used, and incidence of chorioamnionitis and postpartum hemorrhage. Univariate and multivariate logistic regression analyses were used to estimate risks. A secondary analysis was performed on nulliparous patients. RESULTS: A total of 3046 individuals met the inclusion criteria. As body mass index increased, the indications for induction were more likely to be maternal. Rate of achievement of complete dilation decreased with increasing body mass index (973 [88.5%] in the body mass index <30 group vs 455 [70.8%] in the body mass index ≥40 group; adjusted odds ratio, 0.3; 95% confidence interval, 0.2-0.4). The rate of cesarean delivery also increased (149 [13.5%] in the body mass index <30 group vs 207 [30.9%] in the body mass index ≥40 group; adjusted odds ratio, 3.2; 95% confidence interval, 2.5-4.2), as did the time to complete dilation (15.3 hours in the body mass index <30 group vs 18.8 hours in the body mass index ≥40 group; P<.001). Morbidly obese patients required higher doses and more types of induction agents. Misoprostol was used as the sole induction agent in 362 (35.1%) of patients in the body mass index <30 group vs 160 (25.4%) of patients in the body mass index ≥40 group (adjusted odds ratio, 0.6; 95% confidence interval, 0.5-0.8). In the body mass index ≥40 group, a greater number required a combination of misoprostol, mechanical ripening, and oxytocin for induction (147 [14.3%] in the body mass index <30 group vs 158 [25.0%] in the body mass index ≥40 group; adjusted odds ratio, 1.7; 95% confidence interval, 1.3-2.3). For nulliparous patients, the rate of cesarean delivery was significantly higher with increasing body mass index (118 [18.3%] in the body mass index <30 group and 157 [48.2%] in the body mass index ≥40 group; P<.001), with 5 more hours spent in labor (18.3 hours in the body mass index <30 group vs 23.3 hours in the body mass index ≥40 group; P<.001). Nulliparous patients were also more likely to require multiple induction agents (122 [20.3%] for body mass index <30 vs 108 [33.6%] for body mass index ≥40; P<.001). CONCLUSION: Class III obesity is an independent risk factor for nonachievement of complete dilation and vaginal delivery following induction of labor. Furthermore, inductions in these patients require more time and are more likely to require multiple agents.